Synthesis of 4-(organoselenyl) oxazolones via cyclization of N-alkynyl ethylcarbamates promoted by organoselenium. Issue 23 (26th May 2022) - Goulart, Tales A. C.; Recchi, Ana Maria S.; Back, Davi Fernando; Zeni, Gilson
Abstract : Organoselenyl iodide promoted the intramolecular nucleophilic cyclization of N -alkynyl ethylcarbamates in the synthesis of 4-(organoselenyl) oxazolones. Abstract : Organoselenyl iodide promoted the intramolecular nucleophilic cyclization of N -alkynyl ethylcarbamates in the synthesis of 4-(organoselenyl) oxazolones. The reaction was regioselective, giving the five-membered oxazolone products as the unique regioisomer via an initial activation of the carbon–carbon triple bond through a seleniranium intermediate, followed by an intramolecular 5- endo-dig cyclization mode. The generality of the methodology has been proven by applying the optimized reaction conditions to different organoselenyl iodides and N -alkynyl ethylcarbamates having different substituents directly bonded to the nitrogen atom and in the terminal position of the alkyne.